PENGARUH CORPORATE SOCIAL RESPONSIBILITY, ELECTRONIC WORD OF MOUTH DAN KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN DI SOCIAL MEDIA - Widia Irawan; Puspita Chairun Nisa (FEBI UIN Sunan Gunung Djati Bandung, 2023)
The rise of online transportation services is a challenge for companies to offer the best service. This phenomenon is one of the references in the research conducted by the author. The purpose of this study was to determine the effect of corporate social responsibility (CSR), electronic word of mouth (e-wom) and service quality on customer loyalty. The population of this study is people who live in West Jakarta who use online transportation services Grab/Gojek and follow online transportation social media accounts on Facebook/Instagram. The sample in this study was 100 people. The sample selection technique uses a purposive sampling method. The data analysis method used is path analysis through the Partial Least Squares Structural Equation Model (PLS-SEM). Based on the results of testing the data in this study, it can be concluded that corporate social responsibility (CSR) has no effect on electronic word of mouth (e-wom) and customer loyalty. Furthermore, researchers managed to show that electronic word mouth (e-WOM) has an effect on customer loyalty. Then service quality has an influence on electronic word of mouth (e-wom), and service quality shows an influence on customer loyalty.